Effect of Total Asset Turnover (TATO), BOPO, Debt to Asset Ratio Through Firm Size as Moderation Variables on Return on Asset (ROA) at PT Pelabuhan Indonesia (Persero) - Nurwan Bayu Setyawan; Paidi W.S; Gos Ishak (Journal of Social Research, 2023)
The study's primary aim was to examine the influence of total asset turnover (TATO), operating costs on sales (BOPO), debt to asset ratio (DAR), and company size on return on assets (ROA) at PT Pelabuhan Indonesia (Persero) during the period 2015-2021. Quantitative research methods were utilized, and data was directly obtained from the company's financial statements and records for the specified timeframe. Regression analysis, employing moderation variables through the Eviews program, was employed for data analysis. The results indicated that TATO, BOPO, and DAR had a negative impact on ROA at PT Pelabuhan Indonesia (Persero). However, the company size did not significantly moderate the relationship between TATO, BOPO, DAR, and ROA. Additionally, when these factors were collectively considered, their combined effect on the ROA variable was found to be insignificant. In conclusion, the study concluded that specific financial indicators, such as TATO, BOPO, and DAR, adversely affected the company's return on assets, whereas the company size did not play a significant role in moderating these effects. Furthermore, when these factors were analyzed together, their combined impact on the ROA variable was not statistically significant.